Ethical Issues in Interrogating Individuals Involved in Criminal Proceedings During Preliminary Investigation (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
in this scientific article the criminal procedure legislation of our country provides for several moral circumstances, in particular: a) gesture (part 1 of Article 102 of the Criminal Procedure Code); b) refusal of the interrogated person to answer (part 3 of Article 106 of the Criminal Procedure Code). This is the maximum concreteness in our legislation. We can only assume an ethical description of the purpose (task) of a specific issue used in the interrogation. Based on the foregoing, it should be noted that the interrogation provides for the normative legal regulation of issues.